The Role of Small and Medium Enterprises (SME) Innovation and Lifestyle in Enhance Revisit Intention Through Destination Image at Tourist Attraction of Untung Jawa Island - SETIAWAN, Angga; SHIRATINA, Aldina (PT Keberlanjutan Strategis Indonesia, 2023)
This research aims to analyse the role of Small and Medium Enterprises (SME) Innovation and Lifestyle in enhancing Revisit Intention Through Destination Image at the tourist attraction of Untung Jawa Island. The population for this research comprises tourists who have visited Untung Jawa Island at least once, with a sample size of 280 respondents selected using a stratified random sampling method. Data analysis is conducted using Structural Equation Model-Partial Least Squares (SEM-PLS). The study results show that SME Innovation and Lifestyle have a positive and significant influence on Destination Image. Destination Image also has a positive and significant effect on Revisit Intention. Additionally, Lifestyle has a positive and significant impact on Revisit Intention. However, SME innovation has a positive impact, but not a significant effect on Revisit Intention. Overall, the research results indicate that SME Innovation and Lifestyle have a positive and significant effect on Revisit Intention through Destination Image. Destination Image plays an intervening variable between SME Innovation and Lifestyle in relation to Revisit Intention. The implications of this study suggest that the relevant parties of Untung Jawa Island can enhance Revisit Intention by focusing on SME Innovation, Lifestyle, and Destination Image.